Impact of Different Drying Methods on the Acerola-Ceriguela Mixed Pulp: Physicochemical Characteristics, Bioactive Compounds, and Sensory Attributes - Marcony Silva Júnior; Nathalia Silva; Christine Ribeiro; Caio Veríssimo; Ana Paula Rocha; Carlos Grosso; Maria Inês Maciel (Journal of Food Quality)
Fruit mixed pulp has the objective of improving the nutritional and sensorial characteristics, as well as the development of new flavours and aromas. Different methods of drying (e.g., spray-drying, spouted bed drying, and freeze-drying) can influence the quality of the final product. The objective of this study was to select the drying method that enables the production of acerola-ceriguela mixed pulp (ACMP) with higher quality. For this selection, the powder pulps were evaluated for their physicochemical characteristics (water activity, moisture, soluble solids (SS), titratable acidity (TA), SS/TA, and instrumental colour), retention of the bioactive compounds (ascorbic acid, total carotenoids, and phenolic compounds), and sensory evaluation (acceptance, check-all-that-apply (CATA), and intent to purchase). The physicochemical characteristics of the freeze-dried and spray-dried ACMP were nonsignificant p>0.05 but differed significantly p>0.05 from spouted bed powder. ACMP freeze-drying powder resulted in higher retention of ascorbic acid, total carotenoids, and phenolic compounds. The powder obtained by spray-drying showed higher retention of bioactive compounds compared to the spouted bed drying. Therefore, this study suggests that powder obtained by freeze-drying resulted in greater sensorial acceptance.